Hardware Platform Design Analysis of K-Means Clustering Algorithm Implementation - Wahyu Wibowo, Ferry; ., Sudarmawan; Sulistiyono, Mulia (International Journal of Engineering and Technology, 2018)
The K-Means clustering algorithm is an unsupervised data mining technique and it has also been used widely to solve the problem in real life. This paper addresses a design analysis of the algorithm of K-Means that is implemented in the field programmable gate arrays (FPGAs). These devices are integrated circuits and have a hardware platform and applied in many implementations. The K-Means clustering algorithm has a simple method that is choosing objects from data to become the center point or centroid and then assign each object to the cluster which is nearest and update the cluster means. The approach of the software can also be implemented in the hardware, but both of them have a different method in programming.Â Â Â